Effects of different fertilizations on fruit quality, yield and soil fertility in field-grown kiwifruit orchard - Zuoping, Zhao; Min, Duan; Sha, Yan; Zhifeng, Liu; Qi, Wang; Jing, Fu; Yan'an, Tong (International Journal of Agricultural and Biological Engineering, 2017)
Kiwifruit yield and quality and soil nutrients were investigated in a kiwifruit orchard after long-term fertilization to understand the relationship between kiwifruit growth and soil nutrition. Seven fertilization treatments with three replications were applied in a continuous four-year period, including no fertilizer (CK); phosphorus (P) and potassium (K) fertilizers (PK); N and K fertilizers (NK); N and P fertilizers (NP); N, P and K fertilizers (NPK); 1.5 times of N, P and K fertilizers (1.5NPK); and chemical fertilizers plus swine manure (NPKM). Fertilization increased kiwifruit yield at the rate of 450 kg N/hm2, 225 kg P2O5/hm2, 300 kg K2O/hm2. The average yield decreased in a descending order for NPKM (44.6 t/hm2), 1.5NPK (42.6 t/hm2), NPK (42.0 t/hm2), NK (38.0 t/hm2), NP (36.7 t/hm2), PK (36.4 t/hm2) and CK (34.1 t/hm2). The sugar to acid ratio (S:A) was the highest (10.9) in 2012, and the soluble sugar increased by 15.7% after four-year NPKM fertilization. The NPKM fertilization also significantly increased the vitamin C, soluble solid and firmness. The soil organic carbon contents at 0-20 cm, 20-40 cm and 40-60 cm in depth under the NPKM treatment were 27%, 29% and 139% higher than that of the CK treatment, respectively. The available N contents at 0-20 cm, 20-40 cm and 40-60 cm in depth in the 1.5NPK treatment were 180%, 114% and 133% higher than that in the CK treatment, respectively. Balanced fertilization with N, P, K and organic manure is important to soil fertility, which may increase yield and improve quality in field-grown kiwifruit orchard.Keywords: different fertilizations, kiwifruit yield, quality, soil fertilityDOI: 10.3965/j.ijabe.20171002.2569Citation: Zhao Z P, Duan M, Yan S, Liu Z F, Wang Q, Fu J, et al. Effects of different fertilizations on fruit quality, yield and soil fertility in field-grown kiwifruit orchard. Int J Agric & Biol Eng, 2017; 10(2): 162–171.